2006
DOI: 10.1038/sj.onc.1209553
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the dioxin/aryl hydrocarbon receptor (AhR) modulates cell plasticity through a JNK-dependent mechanism

Abstract: Environmental chemicals such as dioxin adversely affect immune, neurological and reproductive functions and have been implicated in cancer development. However, the mechanisms responsible for dioxin toxicity are still poorly understood. Here, we show that dioxin and related pollutants trigger a marked morphological change in epithelial cells that remodel their cytoskeleton to increase interaction with extra cellular matrix while loosening cellcell contacts. Furthermore, dioxin-treated cells show increased moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
101
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 30 publications
5
101
1
1
Order By: Relevance
“…The contribution of AhR to this regulation was assessed using two different approaches; first, we treated the MDA-MB-231 mammary cells, which do not express AhR, with dioxin (see Supplementary information SF3). We did not observe Hef1 mRNA induction as observed with AhR-expressing HepG2 and MCF-7 cells (Diry et al, 2006). Next, we performed AhR mRNA knockdown with our validated siRNAs (Qiagen, Courtaboeuf, France) (see also Figures 1c and d).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The contribution of AhR to this regulation was assessed using two different approaches; first, we treated the MDA-MB-231 mammary cells, which do not express AhR, with dioxin (see Supplementary information SF3). We did not observe Hef1 mRNA induction as observed with AhR-expressing HepG2 and MCF-7 cells (Diry et al, 2006). Next, we performed AhR mRNA knockdown with our validated siRNAs (Qiagen, Courtaboeuf, France) (see also Figures 1c and d).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, alternative mechanisms have been investigated (Mulero-Navarro et al, 2005;Diry et al, 2006). The activation of this receptor has been shown to elicit diverse cellular alterations, including modifications of cell cycle regulation, cell migration and contact inhibition (Mulero-Navarro et al, 2005;Puga et al, 2005;Diry et al, 2006). These alterations could possibly mediate part of the long-term toxicities of the AhR ligands in animals and humans; chronic exposure to several AhR ligands, which are common and persistent pollutants, is frequent in industrialized populations (tobacco smoke, air pollution, food contamination).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanistically, such effects on morphology and migration involved reduced expression of the cellcell interaction protein E-Cadherin and activation of the c-Jun N-terminal kinase (JNK) pathway. 35 In following studies, the same laboratory has further defined the signaling involved in the modulation of adhesion and migration by dioxin. They found that dioxin induces the expression of a member of the Cas family of proteins, Nedd9/Hef1/CasL, 36 which has …”
mentioning
confidence: 99%